English "Pandangan Islam terhadap Hubungan Internasional" - Samih Salah Mohammed (Indonesian Journal of Islamization Studies, 2024)
Islam emphasizes the protection of human dignity and respect for each individual as a result of true humanity. In the Islamic view, society is united under one legal system from the Koran and Sunnah. Islamic legal experts agree that Muslims are united, regardless of differences in territory or position. Islamic law embraces all humanity without discrimination. This research highlights the study of Islam in international relations, emphasizing that Islam is not a collection of separate ideas but a cohesive system rooted in profound principles. The research methodology includes historical and comparative approaches with critical analysis. The theory of realism dominates international relations, viewing it as an arena of unstable conflict, emphasizing national interests, power and war. Islam provides an alternative perspective by affirming justice, peace and cooperation regardless of belief.